Systematics and molecular characterization of new myxosporean species parasites of Colossoma macropomum and Piaractus brachypomus from the Amazon basin and remarks on mitochondrial behavior in myxosporeans - Capodifoglio, Kassia Roberta Hygino (2019)
The Amazon basin has about 7000 km2 of extension and a vast biodiversity providing an ichthyofauna of approximately 5000 species of fish. Myxozoan parasites cause diseases in fish in both the natural environment and the breeding systemand they are responsible for high mortality rates. Myxozoans show a great diversity of species with some of them, highly pathogenic and, therefore, have been receiving attention of the researchers. In Brazil, due to the great diversity of fish species, the study of these parasites has been gaining the attention of the researchers, focusing on diversity, biology and parasite-host interaction. In this context, the objective of this work was to explore the parasite diversity of the Myxozoa subphylum, through morphological and molecular analyses of myxosporean parasites of Amazonian fish, important for the food market such as Colossoma macropomum (tambaqui) and Piaractus brachypomus (pirapitinga). For the taxonomic study, morphological analyses were performed using light microscopy and molecular analyses using ssrDNA. The fish were captured in the Amazon basin, in the Tapajós and Solimões Rivers, Santarém, PA and Manaus, AM, respectively. Two new myxosporean species, Myxobolus n. sp. 1 and Myxobolus n. sp. 2, were described infecting C. macropomum, based on morphological and molecular data. Myxobolus colossomatis, found infecting C. macropomum, was considered a distinct species of Myxobolus cf. colossomatis described in Piaractus mesopotamicus, through molecular and phylogenetic data. For P. brachypomus four new species were described. Henneguya n. sp. 1 and Myxobolus n. sp. 3, were described through of morphological, histological, ultra-structural and molecular analyses. Henneguya n. sp. 2 and Myxobolus n. sp. 4 were described based in morphological and molecular data. After observing the mitochondrial behavior of myxospores through electron microscopy studies, we performed an experiment of mitochondrial fluorescence microscopy and the results showed that few Henneguya sp. myxospores presented labeling for mitochondrial activity.